Movement patterns and metabolic responses during an international rugby sevens tournament - Couderc, A.; Thomas, C.; Lacome, M.; Piscione, J.; Robineau, J.; Delfour-Peyrethon, R.; Borne, R.; Hanon, C. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the running demands and associated metabolic perturbations during an official rugby sevens tournament.